PEMBERIAN ASI EKSKLUSIF TIDAK BERPENGARUH TERHADAP KEJADIAN STUNTING PADA USIA 7-24 BULAN DI DESA KALIKEBO TRUCUK KLATEN - Endang Wahyuningsih; Lilik Hartati; Anggih Puspasari (Stikes Muhammadiyah Klaten, 2021)
Stunting is a condition of failure to thrive in children under five years old (for babies under five years old) caused by chronic malnutrition so that the child is too short for his age. Children are defined as stunted if their height for age is more than two standard deviations below the average Child Growth Standard. One of the risk factors for stunting in children is the lack of nutritional intake for toddlers, especially the best nutritional intake for infants, namely breast milk. Breastfeeding is thought to have an effect on the incidence of stunting. The purpose of this study was to find out how exclusive breastfeeding affects the incidence of stunting at the age of 7-24 months in the village of Kalikebo, Trucuk, Klaten. This type of research uses descriptive correlation with a retrospective approach. The sample in this study was 56 respondents using the sampling technique, namely total sampling. The data taken is secondary data. Bivariate analysis using chi square analysis with p value 0.000 <0.05. The results of the correlation between exclusive breastfeeding and the incidence of stunting showed p value = 0.0834> 0.05. It can be concluded that the results of the study show that there is no relationship between exclusive breastfeeding and the incidence of stunting in Kalikebo Trucuk Village, Klaten.